Analysis of South Africa's ICT policy through developmental state and ICT for development theories - Moyeni, Vusi (My University, 2014)
Developing countries face the challenge of devising ways to advance rapidly through developmental stages. At the turn of the millennium, South Africa focussed its attention on pursuing the twin goals of becoming a ‘developmental state’ and harnessing ICTs to become an advanced inclusive ‘information society’. Despite these pent up aspirations, it has failed to put in place concrete policy enablers and strategies to vigorously pursue these specific goals. Furthermore, while ICT policies express ICT for development (ICT4D) perspectives, few have delivered on their stated objectives. This policy analysis research investigated seven distinct ICT policies (or policy components) published between 2001 and 2012, examining the extent to which they reflect either developmental state or ICT4D themes. The developmental state perspective is based on four sub-themes, namely developmentalist ideology, state capacity and institutional arrangements, state autonomy, and country context. The ICT4D perspective is based on five sub-themes, namely enabling institutional environment, agile ICT industry, robust ICT infrastructure, human digital capability development, and ubiquitous e-services deployment. The findings illustrate that ICT policy fairs reasonably well on only one of the nine sub-themes presented above, namely attention to the enabling institutional environment, even if only at the level of principle. The research report notes further that South Africa is headed towards a captured welfare state rather than a capable competitive developmental state, while the major ICT policies exhibit glaring gaps in terms of reflecting either developmental state or ICT4D theories. Finally, the report proposes a series of new directions for policy thinking on ICT-enabled development.
Thesis (M.M. (ICT Policy and Regulation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2013.
Keywords: ICT; Information technology; Development; Government policy; South Africa